PELATIHAN SISTEM BUDIDAYA SAYUR SECARA HIDROPONIK DI DESA KARANGMULYA - Ibrahim, Saddam Thariq; Muslimah, Alfiana Indah; Rikmasari, Rima (Universitas Islam 45 Bekasi, 2024)
Karangmulya Village has significant potential for sustainable agricultural development; however, it faces several challenges, including limited land availability and a lack of knowledge among residents regarding modern farming techniques. One viable solution is hydroponic cultivation, which allows plants to grow without soil while optimizing water and nutrient use. However, insufficient knowledge and skills in implementing hydroponic systems remain the primary obstacles to its development. This community service program aims to enhance the understanding and skills of Karangmulya Village residents in hydroponic vegetable cultivation. The training was conducted through educational sessions, practical demonstrations, and direct mentoring of participants. The activities included an introduction to the basic principles of hydroponics, various hydroponic system types, plant maintenance techniques, and marketing strategies for harvested produce. The program’s effectiveness was evaluated through observations and interviews conducted before and after the training. The results indicate a significant improvement in participants' knowledge and skills regarding hydroponic systems. Participants were able to comprehend and independently apply hydroponic farming techniques, including building simple hydroponic installations and managing plant nutrition. Additionally, this program fostered interest among residents in developing hydroponics as an efficient and sustainable alternative agricultural business. Through this training, Karangmulya Village residents are expected to maximize local potential and improve their livelihoods through productive and environmentally friendly hydroponic farming practices.